Using computational fluid dynamics in the determination of solar collector orientation and stack height of a solar induced ventilation prototype - Yusoff, Wardah Fatimah Mohammad; Sapian, Abdul Razak; Salleh, Elias; Adam, Nor Mariah; Hamzah, Zabidi; Mamat, M.H.H (UPM Press, 2014)
Stack ventilation in the hot and humid climate is inherently inefficient due to minimal air temperature differences between indoor and outdoor environment of a naturally ventilated building. Solar induced ventilation is a viable alternative in enhancing this stack ventilation. This paper aims to demonstrate investigations on the effective solar collector orientation and stack height for a solar induced ventilation prototype that utilizes roof solar collector and vertical stack. The orientation of the solar collector is significant as it determines the amount of solar radiation absorbed by the solar collector. Meanwhile, the height of the vertical stack influences the creation of the stack pressure in inducing air movement. Investigations were executed using a simulation modelling software called FloVENT. The validation of the simulation modelling against physical experiment indicated a good agreement between these two results. Analyses were executed on the air temperature increments inside the solar collector. A high increment of the air temperature resulted in the effective orientation. Meanwhile, the air temperature and mass flow rate of the various heights of the vertical stack were also analyzed. The findings concluded that the recommended orientation for the prototype’s solar collector is the west-facing orientation. It was also found that the higher the vertical stack, the lower the air temperature inside the stack would be, but with greater induced mass flow rate.